Upaya Penyelesaian Persekusi di Indonesia Menggunakan Pendekatan Analisis Hirarki - La Sugi; Mohammad Sarfan Basyir Putuhena (Mahesa Research Center, 2022)
This article aims to analyze efforts to solve the problem of persecution that often occurs in Indonesia. Persecution is a type of crime against humanity due to the deliberate deprivation of basic rights that is against the law. This article uses a qualitative approach with an Analytical Hierarchy Process from William Dunn (2003) as the unit of analysis. The results of the study indicate that the Possible Causes or causes that cause a problem are due to law (legal culture) and democracy. While the Plausible Causes or reasonable causes that can have a significant influence on the two causes are disobedience to law, universal truth claims, and majority domination. So that Actionable Causes or what needs to be followed up by the government in overcoming the problem of persecution is optimizing legal education and the state is obliged to provide protection for citizens.